2012
DOI: 10.1186/1757-7241-20-48
|View full text |Cite
|
Sign up to set email alerts
|

The clinical consequences of a pre-hospital diagnosis of stroke by the emergency medical service system. A pilot study

Abstract: BackgroundThere is still a considerable delay between the onset of symptoms and arrival at a stroke unit for most patients with acute stroke.The aim of the study was to describe the feasibility of a pre-hospital diagnosis of stroke by an emergency medical service (EMS) nurse in terms of diagnostic accuracy and delay from dialing 112 until arrival at a stroke unit.MethodsBetween September 2008 and November 2009, a subset of patients with presumed acute stroke in the pre-hospital setting were admitted by EMS sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 15 publications
3
13
0
Order By: Relevance
“…The identification of a suspected acute stroke and TIA in the prehospital setting is an important yet challenging task. Previous studies have shown that between 30% and 45% of patients with a field diagnosis of stroke do not have the diagnosis confirmed at hospital . Several stroke recognition instrument tests have been introduced, and most of these tests include the three symptoms of facial weakness, arm weakness, and speech disturbance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The identification of a suspected acute stroke and TIA in the prehospital setting is an important yet challenging task. Previous studies have shown that between 30% and 45% of patients with a field diagnosis of stroke do not have the diagnosis confirmed at hospital . Several stroke recognition instrument tests have been introduced, and most of these tests include the three symptoms of facial weakness, arm weakness, and speech disturbance.…”
Section: Discussionmentioning
confidence: 99%
“…This includes the dispatch center and the emergency medical service (EMS). The link dealing with the EMS is dependent on the early identification of stroke by the EMS clinician . Stroke is characterized by the sudden loss of cerebral function, and there are a variety of symptoms in acute stroke, such as hemiparesis or aphasia.…”
Section: Introductionmentioning
confidence: 99%
“…Since EDs cannot have any influence on the external factors of ED crowding, the focus should be more on internal factors, including their organisational and professional patterns. Amongst many suggestions in the literature, fast‐track and flexible‐care areas have gained popularity because of positive outcomes . Another approach with good global outcomes is the introduction of walk‐in centres and co‐located GPs, which have resulted in lower waits time compared with EDs without a GP .…”
Section: Discussionmentioning
confidence: 99%
“…Amongst many suggestions in the literature, fast-track and flexiblecare areas have gained popularity because of positive outcomes. 13,41 Another approach with good global outcomes is the introduction of walk-in centres and co-located GPs, 41 which have resulted in lower waits time compared with EDs without a GP. 42 The impact of GP-led walk-in centres on demand for ED care was studied in a British report, showing a significant reduction of 8.3% in GP-type presentations to adult EDs.…”
Section: Discussionmentioning
confidence: 99%
“…Such a reduction is of course dependent on local factors, i.e. the logistics in the local hospital where the study took place [ 17 , 19 , 20 ]. Therefore our results cannot be extrapolated to other hospitals either inside or outside Sweden.…”
Section: Discussionmentioning
confidence: 99%